Simultaneous Activation of Iron- and Thiol-Based Sensor-Regulator Systems by Redox-Active Compounds - Lee, Kang-Lok; Yoo, Ji-Sun; Oh, Gyeong-Seok; Singh, Atul K.; Roe, Jung-Hye (Frontiers in Microbiology, 2017)
Bacteria in natural habitats are exposed to myriad redox-active compounds (RACs), which include producers of reactive oxygen species (ROS) and reactive electrophile species (RES) that alkylates or oxidizes thiols. RACs can induce oxidative stress in cells and activate response pathways by modulating the activity of sensitive regulators. However, the effect of a certain compound on the cell has been investigated primarily with respect to a specific regulatory pathway. Since a single compound can exert multiple chemical effects in the cell, its effect can be better understood by time-course monitoring of multiple sensitive regulatory pathways that the compound induces. We investigated the effect of representative RACs by monitoring the activity of three sensor-regulators in a model actinobacterium Streptomyces coelicolor; SoxR that senses reactive compounds directly through oxidation of its [2Fe-2S] cluster, CatR/PerR that senses peroxides through bound iron, and an anti-sigma factor RsrA that senses RES via disulfide formation. The time course and magnitude of induction of their target transcripts were monitored to predict the chemical activities of each compound in S. coelicolor. Phenazine methosulfate (PMS) was found to be an effective RAC that directly activated SoxR and an effective ROS-producer that induced CatR/PerR with little thiol-perturbing activity. p-Benzoquinone was an effective RAC that directly activated SoxR, with slower ROS-producing activity, and an effective RES that induced the RsrA-SigR system. Plumbagin was an effective RAC that activated SoxR, an effective ROS-producer, and a less agile but effective RES. Diamide was an RES that effectively formed disulfides and a weak RAC that activated SoxR. Monobromobimane was a moderately effective RES and a slow producer of ROS. Interestingly, benzoquinone induced the SigR system by forming adducts on cysteine thiols in RsrA, revealing a new pathway to modulate RsrA activity. Overall, this study showed that multiple chemical activities of a reactive compound can be conveniently monitored in vivo by examining the temporal response of multiple sensitive regulators in the cell to reveal novel activities of the chemicals.